A review of in-situ optical flow measurement techniques in the Deepwater Horizon oil spill. (1st March 2020) - A.B., Osman; Ovinis, Mark
Abstract: The ability to estimate the flow rate of an oil spill from a well blowout is crucial in determining the appropriate type of response and containment method, as well as to gauge the efficacy of any well kill technique. In the Deepwater Horizon Macondo well blowout incident, in situ video observations were used to estimate the flow rate of the oil spill. This paper reviews these optical techniques applied for in-situ flow measurement which are feature tracking velocimetry, particle image velocimetry, optical plume velocimetry (OPV). Their working principles, advantages and limitations are discussed from a fundamental point-of-view. Among these techniques, OPV had the least uncertainty, as it time-averaged the flow. A promising technique, known as wavelet-based optical velocimetry, is briefly reviewed and its potential application for flow estimation is discussed.